A COMPARATIVE STUDY BETWEEN CORE STABILIZATION AND SUPERFICIAL STRENGTHENING EXERCISES FOR THE TREATMENT OF LOW BACK PAIN IN TWO WHEELER RIDERS - TUSHAR. J. PALEKAR, M.P.T,; ARIJIT KUMAR DAS , M.P.T,; VENUS. K. PAGARE, M.P.T, (International Journal of Pharma and Bio Sciences, 2015)
Low back Pain (LBP) is a major musculoskeletal problem affecting the two wheeler riders. Various factors have been implicated, including lack of/uncomfortable lumbar support, the long time spent in one position, poor conditions of the road and exposure to whole body vibration (WBV). In addition to these extrinsic factors, alteration in neuromuscular control of core stabilizers and/or poor strength of the superficial muscles has also been considered to predispose an individual to LBP. Thus, present study compared the effectiveness of core stabilization v/s superficial strengthening on pain, health outcome and Transversus abdominis (TrA) activation capacity in two wheeler riders with LBP. 52 subjects were randomly allocated to either of two groups. Exercises were done after 6 weeks, 4 times in a week, each session lasting 30 minutes. Results revealed that both exercise protocols are equally effective in reducing pain and improving health outcome. However, core stabilization exercises were more effective in improving TrA activation capacity.